Nilai Pendidikan Karakter Kearifan Lokal berbasis Pemberdayaan Masyarakat pada Kampung Adat Kuta Ciamis - Swaradesy, Rufus Goang; Rojibillah, Isnan; Septiani, Sophia (Universitas Mathla'ul Anwar Banten, 2024)
The government has observed that the formation of national character through education at all levels of education, but its implementation has not shown optimal results. One of the character education strengthening programs launched by the government is character education based on community empowerment. This study discusses local wisdom that is still adhered to by the indigenous people of Kuta Village, Ciamis as the Strengthening of Local Wisdom Character Education Based on Community Empowerment. In this study, a qualitative approach was used with a descriptive method. Data collection techniques in the form of literature studies, observations, interviews, and documentation studies. The data obtained were then analyzed by means of data reduction, data presentation, and drawing conclusions. The results of the study showed that the indigenous people of Kuta Village in their daily lives reflect the main character values ​​contained in the Strengthening of Character Education. These character values ​​include religious, nationalist, mutual cooperation, independent, integrity, and mutual cooperation. The manifestation of these character values ​​can be seen in their lives through several activities, namely local wisdom field schools, revitalization of art preservation, and development of UMKM based on the potential of existing natural resources. Keywords: Character Education Values, Local Wisdom, Community Empowerment, Kuta Village